2020
DOI: 10.1111/tpj.14850
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of 1298 RNA‐Seq samples and construction of a comprehensive soybean (Glycine max) expression atlas

Abstract: SUMMARY Soybean (Glycine max [L.] Merr.) is a major crop in animal feed and human nutrition, mainly for its rich protein and oil contents. The remarkable rise in soybean transcriptome studies over the past 5 years generated an enormous amount of RNA‐seq data, encompassing various tissues, developmental conditions and genotypes. In this study, we have collected data from 1298 publicly available soybean transcriptome samples, processed the raw sequencing reads and mapped them to the soybean reference genome in a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 77 publications
1
47
0
Order By: Relevance
“…The genes in the fraction with the broadest expression patterns were enriched in the GO categories "photoperiodism, flowering" and "protein transporter activity", while those in the fraction with the narrowest expression patterns were enriched in "serine-type endopeptidase inhibitor activity", "negative regulation of endopeptidase activity", and "endomembrane system" (Table S8). RNA-seq data, especially high-resolution transcriptome maps, are an important resource for the identification of stably expressed genes, which are useful as reference genes for qRT-PCR (Zhou et al, 2017;Machado et al, 2020). We used the standard deviation of gene expression divided by mean expression (standard deviation; SD)/mean) as a measure of expression stability, and we identified 20 transcripts with SD/mean ratios < 0.2, 205 with ratios < 0.25, and 720 with ratios < 0.3.…”
Section: Resultsmentioning
confidence: 99%
“…The genes in the fraction with the broadest expression patterns were enriched in the GO categories "photoperiodism, flowering" and "protein transporter activity", while those in the fraction with the narrowest expression patterns were enriched in "serine-type endopeptidase inhibitor activity", "negative regulation of endopeptidase activity", and "endomembrane system" (Table S8). RNA-seq data, especially high-resolution transcriptome maps, are an important resource for the identification of stably expressed genes, which are useful as reference genes for qRT-PCR (Zhou et al, 2017;Machado et al, 2020). We used the standard deviation of gene expression divided by mean expression (standard deviation; SD)/mean) as a measure of expression stability, and we identified 20 transcripts with SD/mean ratios < 0.2, 205 with ratios < 0.25, and 720 with ratios < 0.3.…”
Section: Resultsmentioning
confidence: 99%
“…RNA-seq data, especially high-resolution transcriptome maps, are an important resource for the identification of stably expressed genes, which are useful as reference genes for qRT-PCR (Zhou et al, 2017;Machado et al, 2020). We used the standard deviation of gene expression divided by mean expression (standard deviation; SD)/mean) as a measure of expression stability, and we identified 20 transcripts with SD/mean ratios < 0.2, 205 with ratios < 0.25, and 720 with ratios < 0.3.…”
Section: Buckwheat Transcriptome Atlas and Fesctrava Databasementioning
confidence: 99%
“…'Williams 82', and characterized their expression under dehydration and salt stress. Recently, Machado et al (2020) analyzed 1 298 RNA-Seq samples and constructed a comprehensive soybean (Glycine max) expression atlas. They found that 94% of the annotated genes (52 737/56 044) had detectable expression in at least one sample.…”
Section: Bacterial Diseasesmentioning
confidence: 99%